Przemiana – społeczna i osobista. „Chłop polski” jako przyczynek do analizy współczesnych przemian w szkolnictwie wyższym na świecie - Joseph C. Hermanowicz, Joseph C. Hermanowicz (Człowiek i Społeczeństwo, 2019)
The present work represents an extrapolation of Wiliam I. Thomas and Florian Znaniecki’s study, The Polish Peasant in Europe and America, on behalf of the development of sociological theory. The subject consists of careers and institutions in higher education. The curriculum vitae serves as the novel human document by which to investigate both social and personal change. Academic careers are studied by virtue of their objective and subjective dimensions. Objectively, the institution of education is revealed for the shifting expectations that govern work in academia in specific historical times (indicated by the cohort in which academics earned their Ph.D.s) and in specific socially bound places (indicated by the type of university in which academics work). Major social change in education likely spells personal change for the way in which people subjectively experience the contemporary academic career. The data come from U.S.-based academics; parallel transformational changes are observable globally. The global change discussed in the work centers on diffusion and institutionalization of the research role. The sources and consequences of this change are problematic. Akin to Thomas and Znaniecki’s larger analytic aims, patterns of change are used inductively to formulate theory: the paper culminates by postulating a theory of increasing tendencies in the way knowledge is produced in higher education institutions throughout the world.